Annular two-phase flow in vertical smooth and corrugated pipes. (December 2018) - van Eckeveld, A.C.; Gotfredsen, E.; Westerweel, J.; Poelma, C.
Highlights: Two-phase flow in smooth and corrugated pipes is studied experimentally, in the low liquid loading regime. Development of a novel PLIF implementation to reduce the influence of reflections on film thickness measurements. A corrugated pipe wall results in a strong increase of liquid entrainment, compared to a smooth pipe. The entrainment rate correlates with the amount of liquid accumulating in the cavities of the corrugated wall. Liquid cavity filling scales with the Weber number and the liquid film Reynolds number. Abstract: Two-phase flow in ribbed or corrugated pipes is of interest in many industrial applications. Experiments are performed to assess the flow regime characteristics in upward annular flow through vertical smooth and corrugated pipes. From high speed recordings, the flow regime and temporal film characteristics are obtained. A novel implementation of a planar laser-induced fluorescence (PLIF) method is used to measure the film thickness, preventing strong reflections from deteriorating the measurements. Liquid accumulation between the ribs of the corrugated pipe is also measured using a PLIF technique. Furthermore, droplet sizing is performed combining shadowgraphic and interferometric techniques to capture a large droplet size range. The measurements show that the presence of pronounced corrugations at the pipe wall causes a strong increase in entrainment of liquid into the gas flow. The entrainment is correlated to the filling of the corrugations with liquid; it is significantly reduced (from 90% entrainment to 50%) when the corrugations are entirely filled with liquid. The amount of liquid filling of the corrugations is related to the superficial liquid film flow velocity. The liquid filling fraction ( α ) scales with the Weber and liquid Reynolds number, and the obtained scaling also holds when the experiments are repeated with a different liquid (mono-ethylene glycol) and with a larger corrugation geometry. Droplets occurring in corrugated pipe flow are 30–50% larger compared to the smooth pipe, as a consequence of the locally (at the locations of the cavities) increased film thickness.